Photothermal treatment of liver cancer with albumin-conjugated gold nanoparticles initiates Golgi Apparatus–ER dysfunction and caspase-3 apoptotic pathway activation by selective targeting of Gp60 receptor - Mocan L (Dove Medical Press, 2015)
Lucian Mocan,1,2 Cristian Matea,1 Flaviu A Tabaran,3 Ofelia Mosteanu,1,4 Teodora Pop,1,4 Teodora Mocan,1,5 Cornel Iancu1,2 1Nanomedicine Department, Regional Institute of Gastroenterology and Hepatology “Octavian Fodor”, 2Department of Surgery, University of Medicine and Pharmacy, “Iuliu Hatieganu”, 3Department of Pathology, Faculty of Veterinary Medicine, University of Agricultural Sciences and Veterinary Medicine, 4Department of Gastroenterology, 5Department of Physiology, University of Medicine and Pharmacy, “Iuliu Hatieganu”, Croitorilor, Cluj-Napoca, Romania Abstract: We present a method of enhanced laser thermal ablation of HepG2 cells based on a simple gold nanoparticle (GNP) carrier system such as serum albumin (Alb), and demonstrate its selective therapeutic efficacy compared with normal hepatocyte cells. HepG2 or hepatocytes were treated with Alb-GNPs at various concentrations and various incubation times, and further irradiated using a 2 W, 808 nm laser. Darkfield microscopy and immunochemical staining was used to demonstrate the selective internalization of Alb-GNPs inside the HepG2 cells via Gp60 receptors targeting. The postirradiation apoptotic rate of HepG2 cells treated with Alb-GNPs ranged from 25.8% (for 5 µg/mL) to 48.2% (for 50 µg/mL) at 60 seconds, while at 30 minutes the necrotic rate increased from 35.7% (5 µg/mL) to 52.3% (50 µg/mL), P-value <0.001. Significantly lower necrotic rates were obtained when human hepatocytes were treated with Alb-GNPs in a similar manner. We also showed by means of immunocytochemistry that photothermal treatment of Alb-conjugated GNPs in liver cancer initiates Golgi apparatus–endoplasmic reticulum dysfunction with consequent caspase-3 apoptotic pathway activation and cellular apoptosis. The presented results may become a new method of treating cancer cells by selective therapeutic vectors using nanolocalized thermal ablation by laser heating. Keywords: liver cancer, gold nanoparticles, HepG2 cells, functionalization, laser irradiation, albumin